Nutritional Status Evaluation in Surgical and Orthopedics Patients, Srinagarind Hospital: 3B ward - Tantiyasawatdikul, Jitaree; Jadnok, Bantita; Tijana, Sarunya; Phetcharat, Tarinee (Srinagarind Medical Journal, 2019)
Background and objectives: Nutritional status evaluation are important factors before, during, and after operation, which could improve wound healing, increase immune system, reduce infection, reduce length of stay in hospital, and reduce the cost of hospitalization. Screening of nutritional status of patients in surgical and orthopedics department (3B ward) could become the database for developing the guideline for treatment of interdisciplinary team. Method: This was a descriptive study, to evaluate the nutritional status of 86 patients admitted in 3B ward during 2014-2015.The instruments used in this study consisted of 1) questionnaires of personal data 2) screening assessment of nutrition status 3) questionnaires of nutrition assessment including Mid-Arm Circumference (MAC), Triceps Skin Fold Thick (TSF), Mid-Arm Muscle Circumference (MAMC), and total lymphocyte. All data was reported as frequency, mean, and percentage. Results: 86 patients were recruited with aged range between 22-81 years old, mean age of 52.9 years old. 90.70% of patients were married and 55.81% of patients were female. Patients took regular diet and had no problem of oral cavity 70.93% and 87.21%, respectively. The results found that 12.79 % of patients had high risk of malnutrition, which identified as cardiovascular disease and cancer of 45.45% and 36.36%, respectively. The patients had high risks of malnutrition in terms of Triceps Skin Fold Thick (TSF), Mid-Arm Muscle Circumference (MAMC), and total lymphocytes assessment at 36.36%, 9.09%, and 36.36%, respectively. Conclusion: Screening nutritional status in surgical 3B ward was found to have high risk of malnutrition, particularly patients with cardiovascular diseases and cancers. However, there was no problem of nutrition status for patients with oral cavity and eating.